Bicycle safety in Bogotá : a seven-year analysis of bicyclists' collisions and fatalities (2019)
"Bicyclists are one of the most vulnerable road agents in the city of Bogotá, with an SMR of 2.09 in 2017. In this study we aim to determine the existence of spatiotemporal trends of standardized collisions and mortality rates, and to identify the individual and contextual risk factors affecting the probability of a fatal outcome in bicyclists' collisions to support policy decision making. We use linear trends, point pattern analysis, and a multilevel gener-alized additive mixed model (GAMM) to estimate the effects of risk factors on the probability of bicyclists' fatalities. Our sample comes from Bogotá's Secretariat of Mobility and data compiled by Fundación Despacio and World Resources Institute. Our findings indicate that, for Bogotá, cyclists' mortality is associated with demographics, the vehicle type involved, and contextual factors as the terrain slope. Our empirical results show evidence of an existing gender gap in bicycling safety patterns."--Tomado del Formato de Documento de Grado.